Analisis Keuangan untuk Menilai Kinerja Perusahaan Rasio PT Hutama karya - Budi Dharma; Nurul Hayati Panjaitan; Khori Ayu Tridyanthi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study was to analyze financial performance based on the ratio of PT. Hutama Karya, Tbk in the period 2012 to 2017. The data analysis technique used in this study is descriptive analysis with a qualitative approach. The results obtained are the financial performance of PT. Hutama Karya, Tbk from 2012-2017 fluctuated every year. The effect of fluctuations in the financial ratios of PT. Hutama Karya, Tbk from 2012-2017 was influenced by several external and internal factors of the company itself, so that new steps were needed to improve the company's performance carried out by PT. Hutama Karya, Tbk to be able to answer market needs and be close to the market itself.